Bridging the Research to Application Divide: Recommendations for Community-Based Participatory Research in a Military Setting. (1st October 2016) - Shenberger-Trujillo, Jessica M.; Kurinec, Courtney A.
ABSTRACT: Currently, in the United States, of 100 military service members needing behavioral health care it is estimated that around 50 would receive any care and only 30 to 50 would be provided "minimally adequate" care according to clinical, evidence-based standards. The current article discusses the existing gap between research and application and proposed reasons for this disparity. We briefly highlight existing research approaches developed by various disciplines (e.g., public health, psychology, social work) to address the research to application gap and provide example opportunities for the military's use of a community-based participatory approach. We also provide recommendations for a way forward to promote a research approach that utilizes both cutting-edge research methods and the richness of the applied expertise provided by military personnel. The recommended research approach aims to empower those individuals who provide or receive social, behavioral, or mental health services by creating an opportunity to shape the research from inception to implementation.